MANAJEMEN SUMBER DAYA MANUSIA LEMBAGA PENDIDIKAN - Nuraeni Nuraeni (Idaarah: Jurnal Manajemen Pendidikan, 2019)
One important area in education administration/management is related to human resources involved in the process of dynamics of educational institutions, such as teachers and education personnel, namely administrative/structural personnel. Educational human resource management is also called the management of educators and education. Management of educators and education is potential human resources who play a role in realizing national education goals. Starting from the teaching staff and education that entered the educational organization until finally stopping through the HR planning process covering recruitment, selection, placement, compensation, awards, education and training or development and dismissal. Quality of human resources educational institutions determine the results/products/graduates of the educational institution itself.